The Role Of Micro Business Of Market Snacks In Increasing Community Welfare In Tilatang Kamang District - Cahyani, Indah Kurnia; Yulastri, Asmar (Universitas Negeri Padang, 2022)
Efforts to meet the needs of life in order to become prosperous one of which is to build a micro-business of market snacks. The existence of a micro-business of market snacks is expected to be able to help the economy of the surrounding community, but there are still people who have a low economy. The purpose of this study was to describe the level of welfare of the micro-entrepreneurs of market snacks and to describe the role of micro-businesses of market snacks in improving the welfare of the people in Tilatang Kamang District. The type of research used in this research is descriptive qualitative research with data collection techniques of observation, interviews, and documentation, the informants of the research are the owners, employees and the community in Tilatang Kamang District. The results of the study can be seen that the micro business of market snacks in Tilatang Kamang District has a role in improving welfare, it can be seen from the opening of employment opportunities and the existence of these micro businesses, respondents get an increase in income so that they can meet the needs of their families such as the fulfillment of food, health, shelter, needs education for their children and other needs, seen from 22 informants all experienced an increase in welfare.